2007
DOI: 10.1126/science.1147353
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Hexameric DnaB Helicase and Its Complex with a Domain of DnaG Primase

Abstract: The complex between the DnaB helicase and the DnaG primase unwinds duplex DNA at the eubacterial replication fork and synthesizes the Okazaki RNA primers. The crystal structures of hexameric DnaB and its complex with the helicase binding domain (HBD) of DnaG reveal that within the hexamer the two domains of DnaB pack with strikingly different symmetries to form a distinct two-layered ring structure. Each of three bound HBDs stabilizes the DnaB hexamer in a conformation that may increase its processivity. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
303
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(323 citation statements)
references
References 31 publications
14
303
2
4
Order By: Relevance
“…2B). This was consistent with biochemical and structural analysis that three molecules of DnaG interacted with one molecule of DnaB hexamer, inducing a significantly stimulation of DnaB's ATPase activity [7,16,24,25].…”
Section: Investigations On the Effect Of Dnag Bst Dnai Bsu And Ssdnsupporting
confidence: 90%
“…2B). This was consistent with biochemical and structural analysis that three molecules of DnaG interacted with one molecule of DnaB hexamer, inducing a significantly stimulation of DnaB's ATPase activity [7,16,24,25].…”
Section: Investigations On the Effect Of Dnag Bst Dnai Bsu And Ssdnsupporting
confidence: 90%
“…The observation of two resonances is in agreement with the two different chemical environments of the Tby site in crystal structures of the Bst DnaB hexamer in complex with DnaG ( Figure 1B and C). 13 Previous electron microscopy studies of E. coli DnaB had reported hexamers with 3-fold and 6-fold symmetries. 14−16 The observation of two, rather than one, tert-butyl resonances identifies the 3-fold symmetry as the symmetry prevailing for the Bst helicase in solution.…”
Section: ■ Resultsmentioning
confidence: 99%
“…For example, Geierstanger and co-workers have shown that the NMR resonances of the methyl-and CF 3 -groups of pmethoxyphenylalanine (OMePhe) and p-trifluoromethoxyphenylalanine (OCF 3 Phe) can readily be observed after sitespecific incorporation at different locations of a 33 kDa protein. 9 The signals of the newly introduced 13 CH 3 -and CF 3 groups were readily observed in two-dimensional (2D) 13 C HSQC and 1D 19 F NMR spectra, respectively. Similarly, Mehl and co-workers demonstrated that site-specific incorporation of trifluoromethylphenylalanine (CF 3 Phe) produced 1D 19 F NMR spectra that allowed distinction of different ligand-and metalbound states in 48 and 98 kDa homodimers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Whereas Mg 2þ ion stabilizes this native structure, removal of the metal ion by dialysis or chelation causes the DnaB hexamer to dissociate into trimers and monomers (Bujalowski et al 1994). Xray crystallography of the homologous proteins from Geobacillus kaustophilus and Geobacillus stearothermophilus provides a detailed view of this helicase and the relative arrangement of its smaller amino-terminal and larger carboxy-terminal domains (Bailey et al 2007;Lo et al 2009). …”
Section: Dnaa Is the Replication Initiator In Bacteriamentioning
confidence: 99%
“…DnaB IS THE REPLICATIVE HELICASE, AND INTERACTS WITH DnaC TO FORM THE DnaB -DnaC COMPLEX In E. coli, DnaB is the replicative helicase whose native structure is a toroid of six identical subunits oriented in the same direction (RehaKrantz and Hurwitz 1978;Arai et al 1981;Donate et al 2000;Bailey et al 2007). Whereas Mg 2þ ion stabilizes this native structure, removal of the metal ion by dialysis or chelation causes the DnaB hexamer to dissociate into trimers and monomers (Bujalowski et al 1994).…”
Section: Dnaa Is the Replication Initiator In Bacteriamentioning
confidence: 99%